Close Comminuted Fracture in the Shaft of Femur: Managed by Open Reduction and Internal Fixation with Broad Dynamic Compression Plate (DCP) Without Stripping of Periosteum - Islam, Md Nazrul; Hasan, Suzon Al (TAJ: Journal of Teachers Association, 2009)
Management of close comminuted fracture in the shaft of femur in adult is a difficult task. Here we report a case who was managed by open reduction and internal fixation with broad dynamic compression plate without stripping of Periosteum. doi: 10.3329/taj.v15i2.3919 TAJ December 2002; Vol.15(2): 96-97